Establishing a metropolitan transport authority in Istanbul: A new institutional economics framework for institutional change in urban transport. Issue 3 (September 2019) - Canitez, Fatih; Çelebi, Dilay; Beyazit, Eda
Highlights: Proposes an institutional framework for the institutional change initiatives for urban transport. Examines the institutional environment of urban transport systems from a new institutional economics perspective. Gives a case study of Istanbul's project to establish a metropolitan transport authority based on the proposed framework. Provides an overview of the institutional environment for Istanbul's urban transport system. Analyzes the institutional reasons for why the project stalled and offers a new roadmap for institutional change. Abstract: Rapid urban growth and resulting urban transport problems in developing cities trigger major transformative reform attempts. However, these attempts might fail due to ignoring the role of the institutional environment. Changing the governance structure from a fragmented governance structure to a centralized transport authority is such an institutional change that should take into account the surrounding institutional arrangements. In this paper, drawing from new institutional economics (NIE) literature, a new framework for institutional change in urban transport is proposed to guide those institutional initiatives. To materialize the theoretical considerations regarding this institutional change framework, attempts to establish a metropolitan transport authority (MTA) in Istanbul constitute the case study of this paper. Having a population of nearly 15 million people with radically increasing urban transport problems, city of Istanbul has considerable amount of the urban transport governance problems due to its fragmented and weak institutional setting. Based on the developed framework and lessons drawn from the Istanbul case, our results highlight the importance of examining the institutional environment of urban transport systems by identifying the institutional levels in institutional transformation initiatives.